(untitled) (Scientific journal of the Fergana State University, 2024)
Erebidae is considered one of the largest families of the order of cycads. The family includes more than 24 thousand species. Representatives of this family are nocturnal butterflies, and until 2005 it was included in the Noctuidae family. Based on molecular genetic and phylogenetic studies, this family was separated as a separate taxonomic unit - family. Butterflies are a serious pest not only of agricultural crops, but also of plants in natural ecosystems. Butterfly larvae cause serious damage to plant vegetation and productivity. In our research, the distribution, taxonomy and some bioecological features of this butterfly fauna were studied. 9 species belonging to 2 subfamilies and 4 genera of the Erebidae family were recorded in Fergana Valley.